Lyophilization and Sensory Analysis of Traditional Artisan Turkish Cheeses - Ebru Yıldırım; Celal Can Yalçıner; İlkay Yılmaz (International Journal of Gastronomy Research, 2025)
Türkiye boasts a rich cheese culture, shaped by its diverse geographical features and climatic conditions. Currently, 40 types of cheese in Türkiye have received geographical indication status, contributing to both the local economy and gastronomic tourism. This study aims to dry artisan Turkish cheeses using the lyophilization (freeze-drying) method, which is intended to improve shelf life, ease packaging and transport, and enable snack-type consumption while preserving nutritional value. To achieve this, Ezine, Kars Kaşar, Kars Gruyère, Smoked Circassian, and Divle Obruk Tulum cheeses were freeze-dried at -70°C for 24 hours using a lyophilization device. Following the drying process, the sensory properties of the cheeses were evaluated by 10 trained panelists based on attributes, such as color, odor, texture, crispness, aroma, mouthfeel, and overall acceptability. According to the results, all cheese samples received above-average scores (mean ± SD): Ezine: 4.50 ± 1.27; Smoked cheese: 4.50 ± 0.71; Kars Kaşar: 4.60 ± 0.70; Kars Gruyère: 4.09 ± 0.94; Divle Obruk: 4.82 ± 0.40. The findings obtained in this study indicated that consuming cheese in an alternative form is feasible. It was observed that the cheeses retained their color, taste, shape, and aroma, and their potential to return to their original state upon rehydration was also evaluated. This alternative form may contribute to the promotion of traditional Turkish products and increase appeal among younger generations. Further studies focusing on packaging and rehydration can be conducted for commercialization efforts in the future.